70.7k views
4 votes
Consider a voltage v = Vdc + vac where Vdc = a constant and the average value of vac = 0. Apply the integral definition of RMS to prove the formula RMS =√ [Vdc 2 +(RMS of vac) 2 ]. Hint: v2 = [(Vdc) 2 + 2 *vac* Vdc +(vac) 2 ] and the average value of vac* Vdc = 0.

User Ali AzG
by
5.1k points

1 Answer

2 votes

Answer:

Proof is as follows

Proof:

Given that ,
V = V_(ac) + V_(dc)

for any function f with period T, RMS is given by


RMS = \sqrt{(1)/(T)\int\limits^T_0 {[f(t)]^(2) } \, dt }

In our case, function is
V = V_(ac) + V_(dc)


RMS = \sqrt{(1)/(T)\int\limits^T_0 {[V_(ac) + V_(dc)]^(2) } \, dt }

Now open the square term as follows


RMS = \sqrt{(1)/(T)\int\limits^T_0 {[V_(ac)^(2) + V_(dc)^(2) + 2V_(dc)V_(ac)] } \, dt }

Rearranging terms


RMS = \sqrt{(1)/(T)\int\limits^T_0 {V_(dc)^(2) } \, dt + (1)/(T)\int\limits^T_0 {V_(ac)^(2) } \, dt + (1)/(T)\int\limits^T_0 {2V_(dc)V_(ac) } \, dt }

You can see that

  • second term is square of RMS value of Vac
  • Third terms is average of VdcVac and given is that average of
    V_(ac)V_(dc) = 0

so


RMS = \sqrt{(1)/(T)TV_(dc)^(2) + [RMS~~ of~~ V_(ac)]^2 }


RMS = \sqrt{V_(dc)^(2) + [RMS~~ of~~ V_(ac)]^2 }

So it has been proved that given expression for root mean square (RMS) is valid

User Tyler Jones
by
5.7k points